Italian teachers and Technology-Knowledge training - Nicoletta Di Blas; Manuela Fabbri; Luca Ferrari (Firenze University Press, 2018)
This article aims to answer the question "how are Italian teachers trained in technological skills (TK)?", in the framework of the distributed TPACK model. According to this model, different supports and sources interplay in a learning context. The discussion is based on data collected through a questionnaire delivered to more than 1,300 teachers on the job; the focus is, in particular, on lower and upper secondary school teachers. The results show how teachers benefit from a plurality of sources, preferring the "informal" ones.   I docenti italiani e la formazione alle competenze tecnologiche Questo articolo mira a rispondere alla domanda "come i docenti italiani si formano alle competenze tecnologiche", nel quadro di riferimento del modello TPACK distribuito, secondo il quale una varietà di supporti e fonti agisce in un contesto d'apprendimento. La discussione si basa sui dati raccolti attraverso un questionario erogato a più di 1300 docenti in servizio; il focus è in particolare sui docenti di scuola secondaria inferiore e superiore. I risultati mostrano come i docenti fruiscano di una pluralità di fonti, prediligendo quelle "informali".